2016
DOI: 10.1038/srep20373
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and functional alterations of pDCs in lupus-prone mice

Abstract: Plasmacytoid dendritic cells (pDCs) were considered to be the major IFNα source in systemic lupus erythematosus (SLE) but their phenotype and function in different disease status have not been well studied. To study the function and phenotype of pDCs in lupus-prone mice we used 7 strains of lupus-prone mice including NZB/W F1, NZB, NZW, NZM2410, B6.NZMSle1/2/3, MRL/lpr and BXSB/Mp mice and C57BL/6 as control mice. Increased spleen pDC numbers were found in most lupus mice compared to C57BL/6 mice. The IFNα-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
1
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 48 publications
5
37
1
1
Order By: Relevance
“…Consistently, splenic and lymph node pDCs in lupic NZB/W F1 mice have also been shown to display elevated expression of costimulatory molecules, including CD40 and CD86 in pDCs when compared with mice prior to disease onset [41,42], suggesting that the BM-derived pDCs bear similarities to the peripheral circulating pDCs. Similarly, a recent report by Zhou et al has also demonstrated in disease NZB/W F1 mice a higher expression of MHC-II and CD80 in ex vivo splenic and BM pDCs when compared with pre-disease mice [30]. Likely, these peripheral pDCs in disease mice have been continuously exposed to and stimulated by TLR7 stimulating immune complexes in vivo , thus leading to the hyperactivated phenotypes upon ex vivo examination.…”
Section: Discussionmentioning
confidence: 78%
“…Consistently, splenic and lymph node pDCs in lupic NZB/W F1 mice have also been shown to display elevated expression of costimulatory molecules, including CD40 and CD86 in pDCs when compared with mice prior to disease onset [41,42], suggesting that the BM-derived pDCs bear similarities to the peripheral circulating pDCs. Similarly, a recent report by Zhou et al has also demonstrated in disease NZB/W F1 mice a higher expression of MHC-II and CD80 in ex vivo splenic and BM pDCs when compared with pre-disease mice [30]. Likely, these peripheral pDCs in disease mice have been continuously exposed to and stimulated by TLR7 stimulating immune complexes in vivo , thus leading to the hyperactivated phenotypes upon ex vivo examination.…”
Section: Discussionmentioning
confidence: 78%
“…The most current research has shed light into the role for pDCs during the initiation of TLR-mediated inflammation [64]. Various deficiencies that result in depletion of pDCs in mouse models show that when pDCs are absent, the severity of lupus disease is greatly diminished.…”
Section: Inflammatory Effector Cells In Sle: More Than Just Cytokinesmentioning
confidence: 99%
“…pDCs of different mouse strains may have different properties . Here we investigated the pDC difference among NZB, NZW and NZB/W F1 mice.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, the higher production of IFNα in response to CpG observed with some mouse strains was not a result of an intrinsic higher ability of pDC, rather it reflected the higher abundance of spleen pDCs in the mouse strain . We and others had recently found that pDCs from NZB/W F1 mice produce more IFNα in vitro as it confers a survival advantage, compared with those from C57BL/6 mice . However, it is unclear what the functional properties of parent strains are and what contribution of these properties is likely to confer autoimmunity in NZB/W F1 mice.…”
Section: Introductionmentioning
confidence: 89%